Impedance spectroscopy of suspension plasma sprayed hydroxyapatite coatings - Piasecki, Tomasz; Nitsch, Karol; Pawłowski, Lech; Jaworski, Roman (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Impedance spectroscopy was used to investigate the properties of hydroxyapatite (HA) coatings and their dependence on fabrication parameters. The HA layers were deposited on the titanium substrates using suspension plasma spraying. The analysis of the results was performed using equivalent circuit modelling. The HA layers contained crystalline and amorphous phases. The amount of amorphous phase raised with an increase of plasma torch power. The porosity of coatings was investigated by observation of water evaporation process. The conclusion was that samples fabricated with lower torch power had smaller and more complex pores structure.
Optica Applicata, Vol. 39, 2009, nr 4, s. 915-921
Keywords: optyka; impedance spectroscopy; hydroxyapatite; suspension; plasma spraying; porosity